Research on multi‐attribute decision‐making in condition evaluation for power transformer using fuzzy AHP and modified weighted averaging combination. Issue 15 (1st November 2016) - Sun, Lingjie; Ma, Zhao; Shang, Yuwei; Liu, Yingyi; Yuan, Haiwen; Wu, Guoliang
Abstract : Power transformers are of vital importance for the stable operation of power system. Hence, to grasp transformers' health condition is of imminent importance. However, the evaluation of transformers' health condition is bound with fuzzy, uncertainty, and even conflict information. To address these problems, a novel evaluation model for transformer, by integrating the merits of fuzzy set theory, fuzzy analytical hierarchical process (AHP), and modified weighted averaging combination, is proposed in this study. The evaluation model contains four factors: dissolved gas analysis, electrical testing, oil testing, and miscellaneous factors, as well as 20 indices. The evaluation process consists of three steps. First, the fuzzy set theory is used to obtain assessment grades for each quantified indices. Second, the fuzzy AHP using fuzzy preference programming, which extends classical AHP and can better tackle the uncertainty existed in the comparison matrix given by experts, is introduced to calculate the weights of indices. Finally, the assessment is processed through the modified weighted averaging combination, which is able to handle the conflicts among evidences. The proposed method is verified by evaluating a realistic transformer, and the results of field examples indicate that the method can evaluate the transformer health condition effectively.